Proof of two similar matrices have same eigenvalue and a question

**Theorem:**

I've a question regarding the proof of a theorem.

There is a theorem in my linear algebra book that states:

"If $\displaystyle A$ and $\displaystyle B$ are similar $\displaystyle n$ x $\displaystyle n$ matrices, then they have the same eigenvalues."

**Proof of this theorem:**

Let $\displaystyle A$ and $\displaystyle B$ be similar matrices so there exist an invertible matrix $\displaystyle P$ such that $\displaystyle B = P^{-1} A P$

By the properties of determinant it follows that:

$\displaystyle \begin{align*} \lvert{\lambda I - B}\rvert = \lvert \lambda I - P^{-1} A P \rvert =& \lvert P^{-1} \lambda I P - P^{-1} A P \rvert \\ =& \lvert P^{-1} (\lambda I - A) P \rvert \\ =& \lvert P^{-1} \rvert \lvert \lambda I - A \rvert \lvert P \rvert \\ =& \lvert P^{-1} \rvert \lvert P \rvert \lvert \lambda I - A \rvert \\ =& \lvert P^{-1} P \rvert \lvert \lambda I - A \rvert \\ =& \lvert \lambda I - A \rvert \end{align*}$

**My question:**

My question is: why is that

$\displaystyle \lambda I = P^{-1} \lambda I P $

How do you proof that left hand side of this statement is equal to the right hand side?

What property of linear algebra makes this true? I can't figure out the answer for this problem. Is it possible help me finding the answer?

Re: Proof of two similar matrices have same eigenvalue and a question

$\displaystyle \text{det}(P^{-1}AP-\lambda I)=\text{det}(P^{-1}AP-\lambda P^{-1}IP)$

$\displaystyle =\text{det}(P^{-1}(A-\lambda I)P)=\text{det}(P^{-1})\text{det}(A-\lambda I)\text{det}(P)$

$\displaystyle =\text{det}(P^{-1})\text{det}(P)\text{det}(A-\lambda I)=\text{det}(I)\text{det}(A-\lambda I)=\text{det}(A-\lambda I)$

What is $\displaystyle P^{-1}IP$???

It is just I.

Re: Proof of two similar matrices have same eigenvalue and a question

Quote:

Originally Posted by

**dwsmith** $\displaystyle \text{det}(P^{-1}AP-\lambda I)=\text{det}(P^{-1}AP-\lambda P^{-1}IP)$

$\displaystyle =\text{det}(P^{-1}(A-\lambda I)P)=\text{det}(P^{-1})\text{det}(A-\lambda I)\text{det}(P)$

$\displaystyle =\text{det}(P^{-1})\text{det}(P)\text{det}(A-\lambda I)=\text{det}(I)\text{det}(A-\lambda I)=\text{det}(A-\lambda I)$

Thank you so much. I was thinking $\displaystyle \lambda$ as a matrix(I don't know why I was thinking that). That was the error on my part. Sorry about that. Thanks for clarifying that using constant multiplication property of matrices.